Vascular endothelial growth factor improves the therapeutic effects of cyclodextrin in Niemann-Pick type C mice. Issue 5 (3rd September 2019) - Jeong, Min Seock; Bae, Jae-sung; Jin, Hee Kyung
ABSTRACT: Niemann-Pick type C disease (NP-C) is a fatal neurodegenerative disorder caused by a deficiency in the function of the NPC1 gene. Malfunction of this gene/protein leads to progressive accumulation of unesterified cholesterol and sphingolipids in many organs, including the brain. To date, drugs that target pivotal stages in the pathogenic cascade have been tested as monotherapies or in combination with a second agent, showing additive benefits. In this study, we have investigated the effects of combining centrally and systemically administered therapies in a mouse model of NP-C, i.e. overexpression of brain-specific vascular endothelial growth factor (VEGF) in combination with systemic administration of 2-hydroxypropyl-β-cyclodextrin (CD). We found that animals treated using a combination of VEGF and CD showed an improvement in pathophysiology compared to those treated with CD alone or brain VEGF overexpression alone, or non-treated NP-C mice. Combination therapy increased the time period over which NP-C mice maintained their body-weight and motor function, and decreased the abnormal accumulation of lipids. In addition, combination therapy delayed the onset of Purkinje cell loss and reduced neuroinflammation. Taken together, our results demonstrate that combination therapy using VEGF and CD is a promising therapeutic modality for treating NP-C, and suggest that it represents a potential strategy for the treatment of diseases that cause both visceral and brain pathologies.